The effect of lightning-induced electromagnetic waves on the electron temperatures in the lower ionosphere - Atici, Ramazan; Guzel, Esat; Canyilmaz, Murat; Sagir, Selcuk (Academic Publication Council, 2016)
In this study, the heating of the nighttime lower ionosphere due to electromagnetic radiation in the very low frequency (VLF) band that are transmitted by cloud-to-ground (CG) lightning return strokes is investigated. For this purpose, temperature of electrons in lower ionosphere is calculated by using electron energy balance equation, which is obtained by using Maxwellian distribution. In the result of calculations, in 10 V/m of the electrical field for all modes of electromagnetic (EM) wave, it was observed that the electron temperatures increased by about 9000-11000 K at an altitude of about 85-90 km. With an increase in the electric field, it was observed that the altitude, where the maximum temperatures were reached, shifted higher. The Right-Handed mode of the EM wave, unlike other modes was not return based-state to an altitude of 95-100 km. To fully determine the effect of lightning induced electromagnetic waves on the lower ionosphere, considering the effects of polarized modes (Right and Left) can also provide more information.
Keywords: Electron temperature; EM waves; lightning; lower ionosphere; magnetic field